Effects of intraoperative hypothermia on patients undergoing laparoscopic surgery: A retrospective cohort study. - Tashi Penjore; Maliwan Oofuvong; Sunisa Chatmongkolchart; Chanatthee Kitisiripant; Rongrung Rueangchira-Urai; Jaranya Leeratiwong (PLoS ONE)
Objective This study aims to explore the association between intraoperative hypothermia and outcomes in adult patients undergoing laparoscopic surgery. Methods A retrospective analysis of 2048 adult laparoscopic surgery patients treated between 2020 and 2021 was conducted at Songklanagarind Hospital, Thailand. Intraoperative hypothermia, defined as a core temperature below 36°C, was recorded as either one or more than one episode. Patient demographics, clinical information and postoperative outcomes were extracted from the hospital information system. The outcomes were intraoperative and postoperative cardiac arrhythmias, postoperative oxygen requirement, length of post-anesthetic care unit (PACU) stay, and length of hospital stay. Univariate and multivariate logistic/linear regression models were fit to assess the association between hypothermia and outcomes, presented as odds ratio (OR) or beta-coefficient (β) with 95% confidence interval (CI). Results The incidence of intraoperative hypothermia was 34.9%, with 688 experiencing one episode and 27 experiencing multiple episodes. On multivariate analysis, patients with one and more than one episode of hypothermia had an increased risk of intraoperative cardiac arrhythmia compared to normothermic patients (OR [95%CI]: 1.67[1.24,2.25] and 3.65[1.53,8.74], respectively, P<0.001). Normothermic patients and hypothermic patients with more than one-episode had a higher odds of postoperative oxygen requirement compared to hypothermic patients with only one episode (OR [95%CI]:1.32[1.02,1.7] and 2.64[1.1,6.32], respectively, P = 0.019). Hypothermic patients with one and more than one-episode also had longer PACU stays compared to normothermic patients (β[95%CI]:3.82[1.34,6.29] and 12.43[2.29,22.57] minutes, respectively, P = 0.001). No significant differences were observed in the other outcomes. Conclusions Intraoperative hypothermia in laparoscopic surgery is associated with a higher likelihood of intraoperative cardiac arrhythmias, prolonged PACU stay and higher postoperative oxygen requirement. Further research and prospective studies are warranted to validate these results and develop strategies to manage intraoperative hypothermia effectively.